Triterpenoids from Cyclocarya paliurus: structure, biosynthesis, biological activities - Huiting Xi; Zhongwei Liu; Weixiang Xu; Jiexue Zhao; Yuanxing Wang; Jianhua Xie (Food Science and Human Wellness)
Cyclocarya paliurus (Batalin) Iljinskaja, as a unique and rare monocotyledonous plant in Southern China, is a promising and economical Chinese herbal medicine and functional food. People have conducted a number of research on C. paliurus because of its rich triterpenoids. However, no comprehensive review has illustrated the composition and pharmacological activity of triterpenoids from C. paliurus. This review summarizes 177 triterpenoids from different parts of C. paliurus. The structures of compounds were elucidated, and their biosynthesis was inferred. The biological activities of compounds and triterpenoid-rich extracts, including anti-diabetes, antihyperlipidemia, anti-inflammatory, anticancer or cytotoxicity, antioxidation, etc., were discussed. C. paliurus can be an important and valuable supplement to the food market. This review provides a reference for the further research and application of C. paliurus triterpenoids in the fields of foods and pharmaceuticals.